Pemberdayaan Ibu Menyusui melalui Komunikasi dan Informasi Pembuatan Produk Olahan Berbasis Sumber Besi sebagai Upaya Pencegahan Stunting - Nasution, Atika Fadhilah Danaz; Imelda, Imelda (Jurnal Abdimas Kesehatan (JAK), 2025)
Indonesia is one of the countries with multiple nutritional problems, which is characterized by a high prevalence of stunting. Optimal nutritional intake during the breastfeeding phase is one way to prevent stunting. One source of animal protein that can increase Hb levels in breastfeeding mothers is chicken liver. Various research databases have proven that giving chicken liver can increase hemoglobin levels and prevent anemia during pregnancy. The solution to the problem that the intervention team plans is to provide information and effective communication to breastfeeding mothers about the importance of preventing stunting in toddlers by providing assistance. Assistance is carried out in collaboration with Village Cadres and Midwives. The method in this community service activity includes 3 stages starting from preparing an activity plan and coordinating the community service team. The implementation stage by conducting a pretest, Cesting and posttest counseling and providing information on making processed products based on iron (Fe) sources and ending with the evaluation stage. There was an increase in maternal knowledge before and after Cesting counseling. The average score of knowledge of breastfeeding mothers before the intervention was 59.05 with a minimum value of 40 and a maximum value of 80. After the intervention, the provision of stunting prevention videos increased to 92.03 with a minimum value of 80 and a maximum of 100.